The search of new biologically active compounds with antibacterial and antifungal activity among 1,2,4-triazole-3-thiol derivatives with the remnants of thiophene - V. O. Salionov; O. I. Panasenko; Ye. G. Knysh; O. M. Kamyshnyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
The resistance of microorganisms to antimicrobial and antifungal drugs is still an actual issue in the modern world. Therefore, one of the possible ways to solve this problem is the creation of new drugs. Derivatives of 1,2,4-triazole are interesting in this aspect. In addition a lot of information is published in the scientific literature on the prospects of further research but research data on antimicrobial and antifungal action of 4-R-5-(5-bromthiophen-2-yl)-1,2,4-triazole-3-thiols and 4-R-methylidenamino-5-(thiophen-2-yl)-1,2,4-triazole-3-thiols is missing.